TANTANGAN IMPLEMENTASI PENDIDIKAN MULTIKULTURAL BERBASIS BUDAYA LOKAL ACEH DALAM MENUMBUHKAN SIKAP TOLERANSI SISWA - Udrikal Muna; Putri Zaera, Sonia; Siti Mayang Sari; Musdiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesia is a multicultural country characterized by diverse cultural, ethnic, linguistic, and religious backgrounds, requiring an inclusive educational approach to promote tolerance and social harmony. This study aims to describe the implementation of multicultural education based on Acehnese local culture and to identify challenges in its application at SDQU Al-Muyassar. A qualitative descriptive approach was employed, involving the school principal, teachers, and students selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, and analyzed using interactive qualitative data analysis, including data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings reveal that multicultural education has been implemented through daily school practices, teacher role modeling, and learning activities emphasizing values of tolerance, mutual respect, deliberation, and togetherness rooted in Acehnese local culture. However, the implementation remains largely implicit and has not been systematically integrated into formal lesson planning. Challenges include limited pedagogical strategies, the influence of globalization on students’ cultural orientation, and the underutilization of local cultural resources. This study concludes that Acehnese local culture–based multicultural education has strong potential to enhance students’ tolerance when supported by systematic planning and teacher competence.